عن أثر دسترة مبدأ الأمن القانوني على جذب المستثمرين إلى السوق الاستثمارية الجزائرية - فاتح، خلاف (جامعة زيان عاشور الجلفة, 2021)
يشكل مبدأ الأمن القانوني محور اهتمام أصحاب المشاريع الاستثمارية في أقطاب الأرض الأربعة، وذلك بالنظر إلى دوره في تأمين حقوقهم وصيانة توقعاتهم المشروعة، لذا سارعت بعض الدول الجرمانية واللاتينية كألمانيا الاتحادية وإسبانيا إلى تكريس هذا المبدأ في دساتيرها، وهو التوجه الذي أقره التعديل الدستوري الجزائري لسنة 2020 بموجب المادة 34 منه. لحداثة الموضوع في الحقل الدستوري الجزائري، ولأهميته البالغة في مجال الاستثمار جاءت هذه الورقة من أجل بحث مدى مساهمة دسترة مبدأ الأمن القانوني في جذب المستثمرين الأجانب على وجه الخصوص إلى السوق الجزائرية، إذ تبين أن الاعتراف بالقيمة الدستورية للمبدأ سيمنحه حصانة وحماية أفضل، ويخضع له المشرع والقاضي، كما يلغى كل قانون يخالفه عن طريق تحريك الرقابة الدستورية، الأمر الذي سينعكس إيجابيا على جذب للمستثمرين الأجانب إلى السوق الوطنية، وكذا تحسين مناخ الاستثمار في الجزائر، وقد استخدمنا منهج تحليل الموضوع وكذا المنهج الوصفي وأدوات المنهج المقارن، وذلك وفقا لما يحقق الغرض من المقال
The principle of legal security is the focus of attention of the owners of investment projects in the four poles of the earth, in view of its role in securing their rights and maintaining their legitimate expectations in the host country for investment, so some Latin and German countries rushed to dedicate this principle in their constitutions, which is the orientation approved by the Algerian constitutional amendment project For the year 2020, according to Article 34 thereof, and for the newness of the topic and its great importance in the field of investment, this paper came to discuss the extent of the constitution of legal security in attracting foreign investors in particular to the Algerian market, where it was found that recognition of the constitutional value of the principle would give him immunity and better protection This is by ensuring that it is respected in legislation and regulations through constitutional oversight, which will positively reflect on attracting foreign investors to the national market, as well as improving the investment climate in Algeria, and we have used in this the methodology of the subject analysis as well as the descriptive approach and tools of the comparative approach.
Keywords: الأمن الوطني -- الاستثمارات الأجنبية -- الدساتر الجزائرية -- المشاريع التنموية